Variasi Perbandingan Volume Fasa Membran Dan Fasa Internal Serta Konsentrasi HNO3 Dalam Fasa Internal Terhadap Ekstraksi Ion Timbal(II) Menggunakan Teknik Emulsi Membran Cair - Baharuddin Hamzah; Widya Astuti; Suherman Suherman; Siti Rabiah Laonu (Jurnal Akademika Kimia, 2015)
The research about variation of volume ratio of membrane/internal phase and concentration of HNO3 in internal phase on lead(II) extraction by liquid membrane emulsion technique. Volume ratios of the membrane and the internal phases used were 2:1, 2:2, 2:3 and 2:4 while the HNO3 concentrations used were 1M, 2M, 3M and 4M. The chemical used in this extraction was benzoylacetone as chelating agents. The determination of extraction was performed by spectrodirect spectrophotometer. The results showed the largest extraction percentage on the extraction of the ion lead(II) in solution by using emulsion liquid membrane was obtained in the volume ratio of the membrane and the internal phases of 2:3 with HNO3 concentration in the internal phase of 3M. these numbers can extract the ion lead(II) as much as 238 ppm in 180 mL with the extraction percentage of 84.45.